Data from: Species selection favors dispersive life histories in sea slugs, but higher per-offspring investment drives shifts to short-lived larvae - Krug, Patrick J.; Vendetti, Jann E.; Ellingson, Ryan A.; Trowbridge, Cynthia D.; Hirano, Yayoi M.; Trathen, Danielle Y.; Rodriguez, Albert K.; Swennen, Cornelis; Wilson, Nerida G.; Valdés, Ángel A. (Dryad, 2015)
For 40 years, paleontological studies of marine gastropods have suggested
that species selection favors lineages with short-lived (lecithotrophic)
larvae, which are less dispersive than long-lived (planktotrophic) larvae.
Although lecithotrophs appeared to speciate more often and accumulate over
time in some groups, lecithotrophy also increased extinction rates, and
tests for state-dependent diversification were never performed. Molecular
phylogenies of diverse groups instead suggested lecithotrophs accumulate
without diversifying due to frequent, unidirectional character change.
Although lecithotrophy has repeatedly originated in most phyla, no adult
trait has been correlated with shifts in larval type. Thus, both the
evolutionary origins of lecithotrophy and its consequences for patterns of
species richness remain poorly understood. Here, we test hypothesized
links between development mode and evolutionary rates using
likelihood-based methods and a phylogeny of 202 species of gastropod
molluscs in Sacoglossa, a clade of herbivorous sea slugs. Evolutionary
quantitative genetics modeling and stochastic character mapping supported
27 origins of lecithotrophy. Tests for correlated evolution revealed
lecithotrophy evolved more often in lineages investing in extra-embryonic
yolk, the first adult trait associated with shifts in development mode
across a group. However, contrary to predictions from paleontological
studies, species selection actually favored planktotrophy; most extant
lecithotrophs originated through recent character change, and did not
subsequently diversify. Increased offspring provisioning in planktotrophs
thus favored shifts to short-lived larvae, which led to short-lived
lineages over macroevolutionary time scales. These findings challenge
long-standing assumptions about the effects of alternative life histories
in the sea. Species selection can explain the long-term persistence of
planktotrophy, the ancestral state in most clades, despite frequent
transitions to lecithotrophy.
Figure S1, 16S secondary structure model for SacoglossaSecondary structure
model for a portion of the mitochondrial large ribosomal subunit rRNA
(16S) gene for Elysia crispata; positions conserved across Mollusca are
bolded.Fig S1, 16S secondary structure model.pdfFigure S2, Alignment of
partial 16S gene sequencesAlignment of partial 16S gene sequences for all
taxa, annotated according to secondary structure. Regions of ambiguous
alignment (indicated by green shaded boxes marked “X”) were manually
deleted prior to analyses.Fig S2, full 16S alignment annotated.pdfFigure
S3, Annotated alignment of partial 28S rDNA sequencesAlignment of a
portion of the nuclear large ribosomal subunit rRNA (28S) gene for all
taxa, showing annotated secondary structure based on features conserved
across Metazoa. Regions of ambiguous alignment (indicated by green shaded
boxes marked “X”) were manually deleted prior to analyses.Fig S3, 28S
alignment annotated.pdfFigure S4, Individual gene trees (a-d), BI
consensus tree (e), and ML tree with two data partitions (f)Supplementary
phylogenetic trees, including individual ML gene trees for each locus
based on partial sequences of the (a) mitochondrial COI (658 bp), (b)
mitochondrial 16S rRNA (404 bp), (c) nuclear 28S rRNA (1392 bp), and (c)
nuclear H3 (328 bp) genes; (e) the BI consensus phylogram; and (f) the ML
phylogram and significant bootstrap support values when using two data
partitions as per PartitionFinder.Fig S4a-f, gene trees, BI consensus, ML
alt partitioned.pdfFigure S5, Collapsed phylogeny showing distribution of
species richness and development modesDistribution of species diversity
among supported clades on the ML phylogeny of Sacoglossa. Traditional
genera or genus-level clades were collapsed in proportion to known species
richness, listed for each group. Species diversity and a pruned tree were
used as inputs for ML tests of state-dependent speciation rates using the
BiSSE model. Larval development mode for terminal taxa are coded as: P,
planktotrophic; L, lecithotrophic; ?, unknown. The number of species with
each development mode (or missing data) is given in parentheses for
collapsed clades or terminals representing multiple taxa, in the same
order (P,L,?). The sum of these values represents the total number of
species known in a clade, including undescribed candidate species
identified in the present work. Red branches indicate shifts in
diversification detected by MEDUSA that are independent of larval
development mode. Traditional families are named to the right of, and
delimited by, colored horizontal bars; bolded family names are
traditionally placed in superfamily Limapontioidea. Select higher clade
names are given on branches.Fig S5, BiSSE tree v4.pdfFigure S6, Posterior
distributions of rate parameters from dependent models of correlated trait
evolutionPosterior distributions of parameters from dependent models of
trait evolution, allowing ECY and development mode to evolve in a
correlated manner. Transition rates are labeled as in Fig. 2. Z =
percentage of time a rate was in the zero bin.Fig S6, dep model rate
dist.tifTable S1, Sampled taxa and collection detailsSpecies names, sample
codes and collection details for sequenced taxa used in phylogenetic
analyses. Blank cells reflect missing information for sequence data
obtained from a public
database.Table_S1_sampled_taxa+collection_details_v6.docTable S2,
Developmental character data for SacoglossaDevelopmental character data
for Sacoglossa including larval development mode, presence/absence and
pattern of extra-capsular yolk (ECY), mean egg diameter (± SD), and mean
larval shell width (± SD) at hatching. Taxa are listed alphabetically by
traditional family within higher clades, and then by binomial name within
family. Generic names in quotation marks denote taxa that do not group
with most other members of the genus to which they are traditionally
assigned.Table_S2_devel_data_v7_refs.xlsTable S3, NCBI accession
numbersAccession numbers from the National Center for Bioinformatics
database for sequences generated and/or analyzed in this
study.Table_S3_accession_nos.xlsTable S4, BiSSE model fit using a pruned
input tree and global estimate of unsampled taxaComparison of BiSSE models
correcting for missing data with a pruned input tree and one overall
estimate of the percentage of unsampled taxa (69%), with either (a) one
rate of character change, or (b) rates of reversal (q10) constrained to be
rare (<1%) relative to gains of lecithotrophy (q01).Table S4, split
BiSSE model fit, % missing taxa.docTable S5, BiSSE parameter estimates
using a percentage of unsampled taxa to correct for missing
dataMaximum-likelihood parameter estimates for BiSSE models, correcting
for missing data using an overall percentage of unsampled taxa (69%). The
ML tree (Fig. 3) was pruned of terminals missing character data, and used
as the input tree for BiSSE analyses with three phylogenetic partitions
across Sacoglossa, and either (A) one rate of character change, or (B)
rates of reversal to planktotrophy (q10) constrained to be rare
(<1%) relative to forward rates (q01). Estimates from the preferred
model are bolded, with alternatives shown in descending order of AIC
scores.Table S5, split BiSSE params, % missing taxa.docTable S6,
References cited in Table 4References cited in Table 4, from which data on
development modes were taken for select clades in Heterobranchia and
Caenogastropoda.Table S6, references v2.doc
Keywords: planktotrophy; species selection; lecithotrophy; development mode